Prevalence of Corneal Astigmatism in Patients before Cataract Surgery in Western China - Wei Ma; Chengguo Zuo; Weirong Chen; Shaoyang Zheng; Jiangang Xu; Ruowen Gong; Maierhaba Mijiti; Kaidiliya Alifu; Lin Ding; Mingkai Lin (Journal of Ophthalmology)
Purpose. To investigate the demographics and distribution of corneal astigmatism before cataract surgery in patients from western China and to compare and analyze these findings with those of patients in southern China. Setting. People’s Hospital of Xinjiang Uygur Autonomous Region. Design. Clinical-based cross-sectional study. Methods. Patients undergoing cataract surgery in the People’s Hospital of Xinjiang Uygur Autonomous Region from February 2012 to August 2019 were recruited. Preoperative keratometric data measured by performing preoperative bilateral partial coherence interferometry (IOLMaster), and patient demographics were recorded and analyzed. Results. This study comprised 12,236 eyes of 7065 patients with a mean age of 64.75 ± 9.66 years, and 52.77% of the patients were female. The mean axial length was 23.14 ± 0.96 mm. Astigmatism ranged from 0 diopters (D) to 6.94 D, with a mean of 1.28 D. Corneal astigmatism was between 0.25 D and 1.25 D in 53.71% of eyes, 1.25 D or higher in 39.06% eyes, and less than 0.25 D in 7.23% of eyes. Astigmatism was with the rule (WTR) in 41.94% of the patients and against the rule (ATR) in 38.80% of patients. The mean flat and steep keratometry measurement was 43.19 ± 1.50 D and 44.24 ± 1.62 D, respectively. After matching, corneal astigmatism in western China was 1.30 ± 1.03 D, and it was significantly higher than that in southern China (0.98 ± 0.67 D, P<0.001). After matching, the proportion of WTR astigmatism was 40.99% in western China, which was also significantly higher than the proportion (26.46%) in southern China (P<0.001). Conclusion. Corneal astigmatism in patients before cataract surgery in western China was mainly between 0.25 D and 1.25 D. Compared with patients in southern China, patients in western China are younger, have a much higher degree of astigmatism, and have a higher proportion of WTR astigmatism.